2021
DOI: 10.3389/fendo.2021.633063
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic Optical Imaging of the Pancreas—Revisiting Pancreatic Anatomy and Pathophysiology

Abstract: The exocrine-endocrine multipart organization of the pancreas makes it an exceedingly challenging organ to analyze, quantitatively and spatially. Both in rodents and humans, estimates of the pancreatic cellular composition, including beta-cell mass, has been largely relying on the extrapolation of 2D stereological data originating from limited sample volumes. Alternatively, they have been obtained by low resolution non-invasive imaging techniques providing little detail regarding the anatomical organization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…Although both LSFM and OPT produced results (on islet dimensions) that were comparable to histological sections when analyzed in 2D (Supplementary Fig. 3), we used OPT as the primary imaging modality in this proof-of-principle study due to its inherent properties of producing isotropic voxels and shorter scan times 29 . As new LSFM setups, approaching isotropic voxels 11 , are being developed, these methods will be well suited for quantitative analysis implementing our approach, with the possibility to provide subcellular resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Although both LSFM and OPT produced results (on islet dimensions) that were comparable to histological sections when analyzed in 2D (Supplementary Fig. 3), we used OPT as the primary imaging modality in this proof-of-principle study due to its inherent properties of producing isotropic voxels and shorter scan times 29 . As new LSFM setups, approaching isotropic voxels 11 , are being developed, these methods will be well suited for quantitative analysis implementing our approach, with the possibility to provide subcellular resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a precise understanding of islet organization throughout the entire organ (including size, distribution, and hormonal composition) is critical to fully appreciate the significance of islet architecture and whole organ pancreatic distribution for normal physiology and disease etiology. In this study, mesoscopic optical 3D imaging approaches 11 were used to provide a whole organ account of the β-cell mass distribution (i.e., islet volume and number, as well as 3D spatial location) across the entire volume of the human pancreas. It has previously been demonstrated that the human islet population is heterogenous with regards to cellular architecture and composition 12 , 13 , and different subtypes of endocrine cells even exist within individual islets 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Введение. Поджелудочная железа (ПЖ) с анатомической точки зрения является очень вариабельным органом, размер, форма, положение и сосудистые структуры которого зависят от многих факторов, в том числе, возраста, пола, ожирения, характеристик заболеваний, поражающих орган (сахарного диабета, злокачественных новообразований, панкреатита) [1,2]. За последние годы тактика хирургического лечения патологии ПЖ изменилась в сторону более агрессивной и радикальной резекции, стали выполняться сложные виды резекций в сочетании с реконструкцией сосудов [3].…”
unclassified